A Review: Nanofiller for Chitosan Membrane in DMFC Application - Muhammad Nur Alam (Hayyan Journal, 2025)
Chitosan, a biodegradable polysaccharide derived from chitin, is emerging as a sustainable, low-cost alternative to perfluorinated membranes (like Nafion®) in Direct Methanol Fuel Cells (DMFCs). However, pristine chitosan membranes suffer from low proton conductivity (~10⁻³ S/cm), excessive methanol crossover, limited thermal and oxidative stability, and poor mechanical strength. To address these challenges, significant attention has focused on reinforcing chitosan matrices with nanofillers—such as nanosilica, titanium dioxide (TiO₂), carbon nanotubes (CNTs), graphene oxide (GO), and sulfur- or phosphorous-doped nanoparticles—to tune hydrophilicity, proton transport pathways, and mechanical integrity.This review evaluates synthesis strategies, nanofiller types, and their concentration effects on key membrane properties. Fabrication techniques center on dispersion of nanofillers into chitosan–acid solutions, casting, drying, and crosslinking with agents like glutaraldehyde or tetraethyl orthosilicate (TEOS). Characterizations include SEM/TEM imaging for morphology, mechanical testing for tensile strength and elongation, proton conductivity via electrochemical impedance spectroscopy, methanol permeability assays, and thermal/oxidative resilience through TGA and Fenton’s reagent exposure.Findings demonstrate that silica and TiO₂ nanocomposites can elevate proton conductivity to ~10⁻² S/cm, while reducing methanol permeability to the order of 10⁻⁷ cm²/s. Conductive carbon nanofillers (CNTs, GO) introduced interconnected proton channels, further enhancing conductivity, though at potential cost to homogeneity.